Religious Indifference and Lived Atheism: The ‘Religious Pulse’ of the World at Present - Paul Rohan, J.C. (Jnana Deepa Vidyapeeth, Pune, India, 2021)
Atheism is marked by its nearness to religion. As a trend it was considered a potential enemy of religion. The rejection of God or any absolute or divine realities and the dismissal of religions as artificial and superfluous to mankind were regarded as the core contents of the atheistic tendencies. Nowadays these contents are replaced by religious indifference and practical non-belief in God and religion. The militant atheism has come to an end and the traditional atheistic tendencies have paved the way for practical ‘lived atheism’ in the form of religious indifference. Thus the decline of faith and the loss of religiosity has become a Weltanschauung. Sensing the ‘religious pulse’ of the current world shows that, it is secularism that is predominating while faith and religion seem to be losing their ground. This calls for immediate remedial measures of reinstating the natural religiosity of mankind which is expressed by ‘Homo religious.’
Keywords: Militant Atheism; Religious Indifference; Weltanschauung; ‘Talked Atheism’; ‘Live Atheism’; Enlightenment; Homo Religiosus